An endochitinase gene expressed at high levels in the stylar transmitting tissue of tomatoes - Harikrishna, K.; Jampates-Beale, Rachanee; Milligan, Stephen B.; Gasser, Charles S. (Springer Verlag, 1996)
A gene (pMON9617; Chi2;1) identified by screening a tomato pistil cDNA library has been found to encode a protein similar in sequence to class II chitinases. Using a baculovirus expression system we show that the Chi2;1 protein is an active endochitinase. The Chi2;1 protein is most similar in sequence to a previously described stylar chitinase (SK2) isolated from potato. Both proteins lack the diagnostic N-terminal cysteine-rich regions and the C-terminal vacuolar targeting signals of class I chitinases and appear to define a novel type of class II endochitinases associated with flowers. Chi2;1 is expressed predominantly in floral organs and its expression within these organs is temporally regulated. The highest level of expression is found in the transmitting tissue of the style where Chi2;1 mRNA begins to accumulate just prior to anthesis. In vegetative tissue, low levels of Chi2;1 mRNA were detected, and these levels did not increase in response to wounding or treatment with ethephon. mRNA from Chi2;1 orthologs was not detected in most other angiosperms tested, even including some members of the Solanaceae, and it is therefore unlikely that Chi2;1 is essential for stylar function. A fragment containing 1.4 kilobase pairs of 5′-flanking DNA from the Chi2;1 gene was shown to drive high-level expression of an attached reporter gene in the styles of transgenic tomatoes. This fragment has utility for engineering expression of other coding regions in styles.